FEATURES FOR APPLYING THE INNOVATION IN THE DEVELOPMENT OF TOURISM INDUSTRY IN UKRAINE - О. Davydova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article defines the role of innovation in the tourism industry. The author’s definition of “innovation in tourism” was proposed. The principles of innovation in tourism were analyzed. The classification of innovations in tourism innovation logistics was developed. Modern examples were given for each type of innovation in tourism.